Phytochemical Screening and Analgesic Activity of Syzygium alternifolium (Wild) - Appala Raju, V.V.S.S.; Ganapaty, S.; Rao Pippalla, S.; Asha Jyothi, V. (Asian Journal of Chemistry, 2010)
Many plant related drugs now has found front seat in treatment of diseases because of their equal efficacy and lesser side effects than the conventional treatment. In the present study, the leaves of Syzygium alternifolium is screened phytochemically as well as pharmacologically for the analgesic activity. In this study, phytochemical evaluation of ethyl acetate extract of leaves was found to have more flavonoid content and pharmacological screening has shown significant analgesic activity.